Pakan Tambahan dan Anabolik Growth Promoter Meningkatkan Kadar Hormon Pertumbuhan Sapi Bali - Adnyani, Ni Made Riska; Suwiti, Ni Ketut; Suartini, I Gusti Ayu Agung; Besung, I Nengah Kerta (Jurnal Veteriner; Vol 21 No 4 (2020), 2020)
This study aims to determine the level of growth hormone given feed supplement and anabolic growth promoter. This research was an experimental research using Complete Random Design (CRD) with three factors. There were feed supplement, anabolic growth promoter, and sampling time. There were 20 young male Bali cattle and they were taken care intensively, divided into 4 group, there were control, feed supplement, anabolic growth promoter, and the combination of feed supplement and anabolic growth promoter for five months, and measured the level of growth hormone each month. The level of growth hormone was detected by using competitive Enzyme Linked Immunosorbent Assay method. The result of the research showed that feed supplement and anabolic growth promoter increased the level of bali cattle growth hormone where feed supplement with anabolic growth promoter (P1G1) was not significantly different than given feed supplement without anabolic growth promoter (P1G0). Providing feed supplement optimally by farmers is highly recommended.